Case Series of COVID-19 Asymptomatic Newborns With Possible Intrapartum Transmission of SARS-CoV-2 - Hascoët, Jean-Michel; Jellimann, Jean-Marc; Hartard, Cedric; Wittwer, Apolline; Jeulin, Hélène; Franck, Patricia; Morel, Olivier (Frontiers in Pediatrics, 2020)
Background: Despite the pandemic, data are limited regarding COVID-19 infection in pregnant women and newborns. This report aimed to bring new information about presentation that could modify precautionary measures for infants born of mothers with a remote history of COVID-19. Methods: We report two infants with possible maternofetal transmission, and four mothers without immunologic reactions. Data were collected from the patient files. Results: One mother exhibited infection signs 10 days before uncomplicated delivery, with negative RT-PCR and no antibody detection thereafter. Another mother exhibited infection 6 weeks pre-delivery, confirmed by nasopharyngeal swab testing with positive RT-PCR, and positive antibody detection (IgM and IgG). Both newborns were asymptomatic but tested positive for nasopharyngeal and stool RT-PCR at 1 and 3 days of age for the first one and at 1 day of age for stool analysis for the second one. Two additional mothers exhibited infection confirmed by positive RT-PCR testing at 28- and 31-days pre-delivery but did not present detectable antibody reaction at the time of delivery. Conclusion: These observations raise concerns regarding contamination risk by asymptomatic newborns and the efficacy of immunologic reactions in pregnant mothers, questioning the reliability of antibody testing during pregnancy.